Educating and Construing the Lived Experiences of Athletes of South Cotabato in the New Normal: Proposed Intervention - Edlyn Cris Villa; Julius Guerrero; Vivencio L. Calixtro Jr (Indonesian Journal of Educational Research and Technology, 2022)
This study explored the lived experiences of athletes of South Cotabato in the new normal. This study was done: (1) to determine the challenges of the athletes, (2) to highlight the positive responses in the situation, (3) to introduce a new framework to cope with the new normal. This study is viewed in the context of the COVID-19 pandemic which is best applied as athletes transition to the new normal. It employed a qualitative research design relatively with the phenomenological approach which includes multiple online in-depth interviews from five participants. The result showed that there is a decrease in the level of physical activities engaged of which is rooted in the number of challenges that athletes are experiencing. Furthermore, significant findings explained the ways of how athletes can cope up, with mobile games as a stress reliever, increased attention in home-based training, increased value in academics, strengthened family relationships, and rest. We also developed a sustainability program that assists coaches, trainers, and parents in monitoring the athletes' well-being during the quarantine period. The study concluded that it has resulted in some negative effects on the athletes’ bodies and in the development of their skills. However, there have been emergent opportunities for positive takeaways, as well. This study provides a framework for athletes and coaches to maintain optimal performance in the new normal.